A Conversation with ... Lobadys Perez (A Conversation with ..., 2026)
Interview “A Conversation with … Lobady Pérez” presents a dialogue between Ute Fendler and the dancer Lobady Pérez, who visited the University of Bayreuth in mid-May 2025 to participate in the workshop “From Oblivion to Memory: Transatlantic Memorial Echoes.” During the conversation, Lobady Pérez reflects on the relationship between dance, memory, and history. He explains how movement can serve as a powerful medium for transmitting cultural heritage and recalling experiences connected to transatlantic histories, particularly those shaped by colonial encounters, migration, and the African diaspora. Pérez also discusses his artistic practice and the role of the body as a site of memory, where personal and collective histories can be expressed and reinterpreted through performance. ******* La entrevista “A Conversation with … Lobady Pérez” presenta un diálogo entre la profesora Ute Fendler y el bailarín Lobady Pérez, quien visitó la University of Bayreuth a mediados de mayo de 2025 para participar en el taller “From Oblivion to Memory: Transatlantic Memorial Echoes.” En la conversación, Lobady Pérez reflexiona sobre la relación entre la danza, la memoria y la historia. Explica cómo el movimiento puede convertirse en un medio poderoso para transmitir herencias culturales y para evocar experiencias vinculadas a las historias transatlánticas, especialmente aquellas marcadas por el colonialismo, las migraciones y la diáspora africana. Pérez también habla de su práctica artística y del cuerpo como un espacio de memoria, donde las historias personales y colectivas pueden expresarse y reinterpretarse a través de la performance. Find out more about the project "Black Atlantic Revisted" at the Africa Multiple Cluster of Excellence hier: https://www.africamultiple.uni-bayreuth.de/en/1_2-Research/Research-Projects/Arts-and-Aesthetics/Black-Atlantic-revisited/May-Exhibition/index.html